Time, the City, and the Literary Imagination
XIX, 270 p.
Keywords: Time, the City, and the Literary Imagination explores the literary representation of time in writing about the city from the late eighteenth century up to the present day. Covering familiar cities (New York, Tokyo, London) as well as those less frequently the subject of analysis (Istanbul, Taiwan, York), the essays consider the connections between time and memory, motion, material space, and melancholy. By engaging with contemporary critical perspectives, as well as concepts such as the ‘spatial turn’, postdigitality, and translocalism, the book offers a new way of reading the literary city by tracing the ways in which the relationship between time and urban space shape literary narratives. Kaley Kramer is Principal Lecturer in English Literature at Sheffield Hallam University, UK. She is the co-editor, with Professor Julie Chappell, of Women During the English Reformations (2014). Her research focuses on belonging, property, and identity in lateeighteenth-century writing. Anne-Marie Evans is Associate Head of School for English Literature at York St John University, UK. Her research focuses on American Literature and material culture in early twentieth-century and contemporary writing. .